Overexpression of membrane receptors in HEK 293 cells for preparation of nanovesicles - Bergqvist, Markus (My University, 2020)
The expression of complex recombinant proteins is often performed in mammalian cell lines, such as the HEK 293 cell line used in this study. In this study a 293-F clone that overexpresses two membrane proteins were developed. The clone was developed with two separate transfections with two different plasmids, one for each membrane protein. The membrane proteins form a membrane receptor that is a part of a family of membrane receptors called integrins. The presence of the two membrane proteins on the surface of the cells was verified with flow cytometry. The functionality of the receptor expressed on the cell was evaluated with an adhesion assay. These assays indicated that the receptors on the cells were functional and specific for the ligand. Furthermore, studies have shown that membrane receptors can be activated by divalent cations, however no experiment successfully activated the receptor and increased its affinity for the ligand in our settings. Extracellular vesicles have because of their biocompatibility been widely studied to be used therapeutically. In this study we used the developed clone expressing both membrane proteins to create EV-like nanovesicles (NV). The NVs were prepared via a serial extrusion protocol. A Western blot and a nano-FCM analysis indicated that the membrane proteins were maintained on the NVs. Even though not tested these NVs could potentially serve as a tissue specific delivery system of therapeutic agents.